Comparison of outcomes of arthrodesis and reconstruction (advancement), posterior tibial tendon with excision of accessory tarsal navicular bone (Kidner procedure) in type 2 accessory navicula. Issue 8 (December 2020) - Zeng, Gang; Hu, Xumin; Chen, Yanbo; Yang, Tao; Qiu, Xuemei; Li, Chunhai; Song, Weidong
Highlights: Local arthrodesis surgery for type 2 accessory navicular (AN) is rarely reported. Outcomes between Kidner and arthrodesis procedures for type 2 AN were compared. Kidner surgery and arthrodesis surgery were an effective treatment for type 2 AN. Abstract: Background: The therapeutic outcome of the local arthrodesis surgery for type 2 accessory navicula (AN) is rarely reported. This study aimed to compare the clinical outcomes between Kidner and arthrodesis procedures for type 2 AN. Methods: Sixteen patients (20 feet) with symptomatic type 2 AN receiving surgical treatment in our hospital between November 2013 and December 2015 were retrospectively included. Ten patients (13 feet) underwent the Kidner surgery (Kidner group) and 6 patients received local arthrodesis procedure (arthrodesis group). Radiographic indices before/after surgery were compared between the two groups. Patient's satisfaction with surgery outcome was evaluated by patient self-assessment questionnaire. Results: The calcaneal pitch angle was significantly increased after surgery in both groups (both p < 0.01), while the talocalcaneal coverage angle and lateral talo-first metatarsal angle were not significantly changed after surgery. There was no significant difference regarding the postoperative changes in the three radiographic indices between the two groups. In the arthrodesis group, 3 patients (4 feet) had an excellent outcome, 2 patients (2 feet) a good outcome, and 1 patient (1 foot) had a fair outcome. In the Kidner group, 6 patients (8 feet), 2 patients (3 feet), 1 patient (1 foot) and 1 patient (1 foot) had excellent, good, fair, and poor treatment outcomes, respectively. The rate of good-to-excellent outcomes was comparable between the arthrodesis group and Kidner group (83% vs. 80%, p = 0.696). Conclusion: Our results suggested that both the Kidner surgery and arthrodesis surgery were an effective treatment for symptomatic type 2 AN.